Peran Dinas Pariwisata dan Kebudayaan Dalam Upaya Pelestarian Kesenian Budaya Lokal - Fitriana Fitriana; Yusuf Adam Hilman; Bambang Triono (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
This report aims to review the role of done by of tourism and culture Ponorogo Regency effort in preserving local culture and local art, Also, to know what just working in the opposite direction as well as supporters of the implementation of the preserving. This is a descriptive qualitative research methodology, by gathering data interviews and documentation. The result of this study tourism agency role in improving the local Ponorogo Regency, culture namely by conducting routine, the festival to the community, socialization the development of their talent interest, young generation and the introduction of culture to other regions. Of the activity will impact the increase in the group of the arts which every year is increasing and stable, it has been achieved due to the efforts of the office of tourism and culture Ponorogo Regency who honored consistently. Also, the introduction of the local culture outside the region attracts tourists from the outside to visit Ponorogo Regency routine performances to see a title particularly Reyog Ponorogo. national festival. But efforts have done there are several local arts in the extract of the agency data decrease the number of people interested and the less. even necessary to special handling